How to evaluate the impact of part-time sick leave on the probability of recovering - Daniela Andrén (Örebro University School of Business, 2009)
This paper presents an econometric framework for analyzing part-time sick leave as a treatment method. We exemplify how the discrete choice one-factor model can address the importance of controlling for unobserved heterogeneity in understanding the selection into part-time/full-time sick leave and the probability to fully recover from a reduced work capacity. The results indicate that part-time sick listing increases the probability to recover compared to full-time sick listing when the expected time to recover is longer than 120 days.
Keywords: I12; J21; J28; 330; part-time sick leave; discrete choice model; selection; unobserved heterogeneity